Organelle specific imaging in live cells and immuno-labeling using resonance Raman probe - Li, Yuee; Heo, Jeongyun; Lim, Chang-Keun; Pliss, Artem; Kachynski, Aliaksandr V.; Kuzmin, Andrey N.; Kim, Sehoon; Prasad, Paras N. (ELSEVIER SCI LTD, 2015)
Raman microspectroscopy is one of the most powerful tools in molecular sensing, offering a non-invasive and comprehensive characterization of the intracellular environment. To analyze and monitor molecular content in specific cellular compartments, different parts of cellular architecture must be unambiguously identified to guide Raman image/spectra acquisition. In this regards, the development of Raman molecular probes, producing spectrally distinct and intense signal is of outmost practical importance. Here we report on a new generation of Raman molecular probes, designed for application in live cells and immuno-labeling, capable of providing unprecedentedly high detection sensitivity through Resonance Raman (RR) enhancement. In contrast to existing Raman markers, the proposed RR reporter is designed to produce RR enhancement under excitation in the visible spectral range, far away from absorption of cellular biomolecules. We show that this concept allows for facile identification of labeled cellular domains, simultaneously with mapping of the macromolecules using spontaneous Raman technique. We demonstrate the breakthrough potential of these RR probes for selective labeling and rapid Raman imaging of membranes as well as mitochondria in live cells. We also show that these resonant Raman probes open the way for Raman-based intracellular immuno-labeling. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MICROSPECTROSCOPY; SPECTROSCOPY; NUCLEOLI; BREAST